(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Today’s lifestyle has become complex and hypercompetitive. Due to hectic work schedule, priorities and fast-pace life, people hardly care about what they eat, how they eat, when they eat. They miss the timelines at times. In addition, getting hygienic food is another challenge. Hence, the manufacturers have come up with edible oils which are more safe with minimum negative impact. They advertise in such manner leading to brands. The present study aims to identify the salient features associated with branded edible vegetable oil. The study is empirical in nature. The statistical tools were applied to collect and analyze the data. The study is significant as it deals with the health consciousness, marketing strategy and consumer perceptions.